Overexpression of far upstream element (FUSE) binding protein (FBP)‐interacting repressor (FIR) supports growth of hepatocellular carcinoma. Issue 4 (31st July 2014) - Malz, Mona; Bovet, Michael; Samarin, Jana; Rabenhorst, Uta; Sticht, Carsten; Bissinger, Michaela; Roessler, Stephanie; Bermejo, Justo Lorenzo; Renner, Marcus; Calvisi, Diego Francesco; Singer, Stephan; Ganzinger, Matthias; et al.
<x xml:space="preserve">Abstract</x> The far upstream element binding protein (FBP) and the FBP‐interacting repressor (FIR) represent molecular tools for transcriptional fine tuning of target genes. Strong overexpression of FBP in human hepatocellular carcinoma (HCC) supports tumor growth and correlates with poor patient prognosis. However, the role of the transcriptional repressor FIR in hepatocarcinogenesis remains poorly delineated. We show that overexpression of FIR correlates with tumor dedifferentiation and tumor cell proliferation in about 60% of primary HCCs. Elevated FIR levels are associated with genomic gains of the FIR gene locus at chromosome 8q24.3 in human HCC specimens. In vitro, nuclear enrichment of FIR supports HCC cell proliferation and migration. Expression profiling of HCC cells after small interfering RNA (siRNA)‐mediated silencing of FIR identified the transcription factor DP‐1 (TFDP1) as a transcriptional target of FIR. Surprisingly, FIR stimulates the expression of FBP in a TFDP1/E2F1‐dependent manner. FIR splice variants lacking or containing exon 2 and/or exon 5 are expressed in the majority of HCCs but not in normal hepatocytes. Specific inhibition of FIR isoforms with and without exon 2 revealed that both groups of FIR splice variants facilitate tumor‐supporting effects. This finding was confirmed in xenograft transplantation experiments with lentiviral‐infected short hairpin RNA (shRNA) targeting all FIR variants as well as FIR with and without exon 2. Conclusion: High‐level nuclear FIR does not facilitate repressor properties but supports tumor growth in HCC cells. Thus, the pharmacological inhibition of FIR might represent a promising therapeutic strategy for HCC patients with elevated FIR expression. (Hepatology 2014;60:1241–1250)